PENGARUH KONSEP DIRI DAN KEMATANGAN VOKASIONAL TERHADAP PEMILIHAN KARIER SISWA - Trisuko Nugroho, Felix (Widya Warta, 2021)
This study aimed to analyze the effect of self-concept and vocational maturity on student career choices. The sample of this study was all students of SMA St. Bonaventura Madiun class XI in the academic year 2019/2020, totaling 97 students. The sampling technique was saturated sampling. The data were obtained using the scale questionnaire method, namely the student career choices scale, self-concept scale, and vocational maturity scale. Data were analyzed using multiple linear regression techniques. Self-concept and vocational maturity had an effect of 58,8% on student career choices. The result of the first minor hypothesis was 4,050 (p> 0,05), the second minor hypothesis was 2,790 (p> 0,05), and the major hypothesis was 10,887 (p> 0,05). Thus, it could be stated that Ho was rejected, and Ha was accepted, which meant that self-concept and vocational maturity had a significant effect on student career choices. Â